"Babies come when they are ready": Women's experiences of resisting the medicalisation of prolonged pregnancy. (February 2019) - Roberts, Julie; Walsh, Denis
Being pregnant beyond one's estimated due date is a relatively common experience and requires complex decisions about whether to induce labour or wait for spontaneous onset. We report a qualitative study undertaken in the UK in 2016. We interviewed fifteen women and eleven more took part in an online focus group. Using thematic analysis, resistance to the medicalisation of prolonged pregnancy was identified as a strong theme. Drawing on the work of Armstrong and Murphy, we identify both conceptual and behavioural resistance in the accounts of women who accepted, delayed or declined induction of labour. Experiential knowledge played a key role in resistance, but women found this was devalued. Some healthcare staff used risk discourse to pressure women to comply with induction protocols but were unwilling to engage in discussion. The social context provided further pressure to produce a baby 'on time', with induction normalised as the way to manage prolonged pregnancy. Online spaces provided additional information and support for women to question the medicalisation of prolonged pregnancy. We end by considering the implications for policies of choice and agency in maternity care as well as the need for additional social support for women who are 'overdue'.